2018
DOI: 10.1111/1541-4337.12410
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Exposures to Common Emulsifiers and Their Impact on the Gut Microbiota: Is There a Cause for Concern?

Abstract: Emulsifiers are commonly used in food processing for the technological purpose of altering the flavor or to improve the texture of foods. Due to their ubiquity, these substances are consumed daily at low levels in the human diet. Recently published in vitro and in vivo studies suggest dietary exposure to emulsifiers modulate the gut microbiota and contribute to the increasing prevalence of metabolic disease. A literature search was conducted which identified eight studies investigating the interaction of sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 62 publications
(200 reference statements)
0
17
0
1
Order By: Relevance
“…Increasing rate of consumption of processed foods and beverages has led to increased use of food additives and processing aids such as emulsifiers, which are meant to enhance the texture, flavor, stability and shelf-life of foods (Roca-Saavedra et al 2018;Vo et al 2019). The hydrophilic and hydrophobic molecular groups in emulsifiers contribute to immiscibility of the formulated liquids, which then lead to much enhanced homogeneity and stability in the final products as found in butter, mayonnaise, dressings, chocolates, ketchups and yogurts (Shah et al 2017;Vo et al 2019). Emulsifiers have been estimated to constitute more than 70% of the world's approved food ingredients (Shah et al 2017), necessitating the importance and use of nanosized emulsifiers in this century.…”
Section: Nanotechnology and Nanoemulsionsmentioning
confidence: 99%
“…Increasing rate of consumption of processed foods and beverages has led to increased use of food additives and processing aids such as emulsifiers, which are meant to enhance the texture, flavor, stability and shelf-life of foods (Roca-Saavedra et al 2018;Vo et al 2019). The hydrophilic and hydrophobic molecular groups in emulsifiers contribute to immiscibility of the formulated liquids, which then lead to much enhanced homogeneity and stability in the final products as found in butter, mayonnaise, dressings, chocolates, ketchups and yogurts (Shah et al 2017;Vo et al 2019). Emulsifiers have been estimated to constitute more than 70% of the world's approved food ingredients (Shah et al 2017), necessitating the importance and use of nanosized emulsifiers in this century.…”
Section: Nanotechnology and Nanoemulsionsmentioning
confidence: 99%
“…Besides, many dietary ingredients, different from macronutrients, can affect the gut microbiome. Enteral diets may contain diverse synthetic dietary emulsifiers and preservatives, including carboxymethyl cellulose, soy lecithin, gum arabic, soy polysaccharide, and various glycerol derivatives that have been linked to intestinal dysbiosis [70]. In this regard, Chassaing et al [71], found that two commonly used dietary emulsifiers, carboxymethyl cellulose and polysorbate-80, caused microbial instability of the gut microbiome in mice, characterized by an increase in the Verrucomicrobia and Proteobacteria phyla.…”
Section: Diet Composition: Effect On Gut Microbiomementioning
confidence: 99%
“…Likewise, in mice, ingestion of drinking water containing the emulsifier/thickener carboxymethylcellulose (a 2% w/v solution for 3 weeks) induced changes to their intestinal structure and promoted leukocyte migration to the intestinal lumen (Swidsinski et al 2009). Exposure to carboxymethylcellulose in this study though [ $ 66 mg/kg bodyweight/day based on a 30g mouse (Vo et al 2019)] is 2-3 times higher than the estimated mean daily exposure seen in the US population (Shah et al 2017). Potential effects of food additives on the gut microbiome have generally been overlooked; however, emerging evidence, mainly from animal studies, suggests that several common food additives, not just emulsifiers, can induce microbiotamediated adverse effects (see Table 3).…”
Section: Widespread Use Of Emulsifiers In the Western Dietmentioning
confidence: 61%
“…Benoit Chassaing and colleagues undertook in vivo animal studies where ingestion by mice of polysorbate 80 at higher concentrations [up to 1% v/v in their drinking water for 13 weeks; about equivalent to 2500 mg/kg bodyweight/day (see Vo et al )] caused depletion of the mucus barrier, allowing for closer apposition between luminal bacteria and the intestinal epithelium. More severe inflammation was observed in colitis‐susceptible interleukin‐10 knockout ( Il10 ‐/‐ ) mice (Chassaing et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation